Building Harmony: Local Wisdom And Technology In Early Childhood Education - Anggreni, Made Ayu; Fachrurrazi, Ahmad (Sean Institute, 2025)
The background of this research departs from the concern that the cultural identity of Indonesian children is increasingly eroded by globalization and technological developments. On the other hand, local wisdom in various regions has great potential to build children's character and cultural identity from an early age. This research aims to examine the role of revitalizing local wisdom in shaping early childhood cultural identity in Indonesia. The method used is a qualitative approach with case studies in several early childhood education institutions that have integrated local wisdom in their curriculum. The results of the study show that the introduction of local wisdom through culture-based learning significantly increases children's understanding and sense of pride in their culture. Through approaches based on folklore, art, and cultural rituals, children can develop a strong sense of identity, which contributes to the formation of their character. The conclusion of this study is that the revitalization of local wisdom in early childhood education is very important to build a solid cultural identity, as well as increase cultural awareness in the younger generation. Therefore, it is important for educational institutions to integrate local wisdom in the curriculum so that children can grow up with a good understanding of their culture.